Assessing the Functional Role of Leptin in Energy Homeostasis and the Stress Response in Vertebrates - Deck, Courtney A.; Honeycutt, Jamie L.; Cheung, Eugene; Reynolds, Hannah M.; Borski, Russell J. (Frontiers in Endocrinology, 2017)
Leptin is a pleiotropic hormone that plays a critical role in regulating appetite, energy metabolism, growth, stress, and immune function across vertebrate groups. In mammals, it has been classically described as an adipostat, relaying information regarding energy status to the brain. While retaining poor sequence conservation with mammalian leptins, teleostean leptins elicit a number of similar regulatory properties, although current evidence suggests that it does not function as an adipostat in this group of vertebrates. Teleostean leptin also exhibits functionally divergent properties however, possibly playing a role in glucoregulation similar to what is observed in lizards. Further, leptin has recently been implicated as a mediator of immune function and the endocrine stress response in teleosts. Here, we provide a review of leptin physiology in vertebrates, with a particular focus on its actions and regulatory properties in the context of stress and the regulation of energy homeostasis.